A balanced review of the status T cell-based therapy against cancer - Marincola Francesco M (Journal of Translational Medicine, 2005)
Abstract A recent commentary stirred intense controversy over the status of anti-cancer immunotherapy. The commentary suggested moving beyond current anti-cancer vaccines since active-specific immunization failed to match expectations toward a more aggressive approach involving the adoptive transfer of in vitro expanded tumor antigen-specific T cells. Although the same authors clarified their position in response to others' rebuttal more discussion needs to be devoted to the current status of T cell-based anti-cancer therapy. The accompanying publications review the status of adoptive transfer of cancer vaccines on one hand and active-specific immunization on the other. Hopefully, reading these articles will offer a balanced view of the current status of antigen-specific ant-cancer therapies and suggest future strategies to foster unified efforts to complement either approach with the other according to specific biological principles.